A unique case of hemi-tongue pseudohypertrophy, necrotizing myopathy, and erythema nodosum - Kota Sato; Yoshiaki Takahashi; Toru Yamashita; Mami Takemoto; Nozomi Hishikawa; Shang Jinwei; Yasuyuki Ohta; Koji Abe (MDPI AG, 2018)
A 46-year-old woman developed slowly progressive tongue weakness with a pseudohypertrophic change on the right side of her tongue. She subsequently developed weakness in her proximal lower extremities, skin erythema and a sustained increase of muscle enzymes at 11 M after the onset. A biopsy of the quadriceps muscle showed necrotizing myopathy and a skin biopsy showed erythema nodosum. The present case showed characteristic clinical manifestations that may represent a rare variant of sarcoidosis.